Design, objectives, and lessons from a pilot 25 year follow up re-survey of survivors in the Whitehall study of London Civil Servants. Issue 6 (June 1998) - Clarke, R; Breeze, E; Sherliker, P; Shipley, M; Youngman, L; Fletcher, A; Fuhrer, R; Leon, D; Parish, S; Collins, R; Marmot, M
Abstract : DESIGN: To assess the feasibility of conducting a re-survey of men who are resident in the United Kingdom 25 years after enrollment in the Whitehall study of London Civil Servants. METHODS: A random sample of 401 study survivors resident in three health authority areas was selected for this pilot study. They were mailed a request to complete a self administered questionnaire, and then asked to attend their general practice to have their blood pressure, weight, and height measured and a blood sample collected into a supplied vacutainer, and mailed to a central laboratory. Using a 2 x 2 factorial design, the impact of including additional questions on income and of an informant questionnaire on cognitive function was assessed. RESULTS: Accurate addresses were obtained from the health authorities for 96% of the sample. Questionnaires were received from 73% and blood samples from 61% of the sample. Questions on income had no adverse effect on the response rate, but inclusion of the informant questionnaire did. Between 1970 and 1995 there were substantial changes within men in the mean blood pressure and blood total cholesterol recorded, as reflected by correlation coefficients between 1970 and 1995 values of 0.26, and 0.30 for systolic and diastolic blood pressure and 0.38 for total cholesterol. CONCLUSION: This pilot study demonstrated the feasibility of conducting a re-survey using postal questionnaires and mailed whole blood samples. The magnitude of change in blood pressure and blood total cholesterol concentrations within individuals was greater than anticipated, suggesting that such remeasurements may be required at different intervals in prospective studies to help interpret risks associations properly. These issues will be considered in a re-survey of the remaining survivors of the Whitehall study.